Refining the Charlson Comorbidity Index for use in long-term care patients - Brijesh Sathian (479264) (2025)
Aim To evaluate the Charlson Comorbidity Index (CCI) for predicting outcomes in elderly long-term care patients. Methods A retrospective cohort study analyzed health records of 172 hospitalized patients (aged ≥60) from Rumailah Hospital’s Geriatrics and Long-term Care Department, Qatar. CCI weights were updated using hazard ratios. Logistic regression and C-statistics assessed mortality outcomes. Results Of the 172 patients, 61.5% were male, and 42% were Qatari. Diabetes without complications was the most common comorbidity (42.5%), while AIDS/HIV was absent. In-hospital or 30-day mortality was 6.3%, and 1-year mortality was 26.4%. Updated CCI weights improved risk prediction for diabetes (weight 6), renal disease (weight 4), and malignancies (weight 6), with myocardial infarction assigned zero weight due to low mortality risk. The revised model achieved a C-statistic of 0.9 for both in-hospital and 1-year mortality, surpassing the original CCI’s scores (0.8–0.9). Conclusions The updated CCI, tailored for Qatar’s long-term care population, improves mortality prediction for conditions such as diabetes and renal disease. This context-specific tool improves risk stratification, underscoring the need for tailored prognostic models in Qatar’s evolving healthcare system. Other Information Published in: The Aging Male License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13685538.2025.2554096